Violence against women and presumption of innocence - Torres Ortega, Ilsse Carolina (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
In this document, the text analyzes the allegations against the punitive nature of vindications in favor of women. The argument runs that to combat gender stereotypes feminism intends to use the most coercive means of the State, including restrictions of the defendant´s rights so to raise the number of punishments and to increase its severity. From the mexican context, the text studies whether the claims in favor of women necessarily imply the weakening of guarantees, undermining particularly the presumption of innocence of those who have been accused of crimes of violence against women.
Keywords: violence; violence against women; feminism; presumption of innocence; criminal process